ANALYSIS OF THE EFFECT OF MARKETING COMMUNICATION MIX ON BRAND LOYALTY OF HONDA HATCHBACK JAZZ CAR CASE STUDY AT HONDA WILTOP DEALERSHIP JAMBI CITY - Garry Yuesa Rosyid (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The structure of the market causes any business to have been conscious of being a winner. Honda dealers Jambi City as one of the businesses that provide marketing should understand in this situation, only how to determine new targeting strategies, increase sales, but also retain customers, because they can affect the increase in revenue. This thesis is to analyze the effect of marketing communication mix on brand loyalty. products from Honda dealers Jambi City, and the elements of the marketing communication mix that have the most significant effect on customer brand loyalty in Jazz hatchback car products at Honda Jambi dealerships. Respondents to the survey were 95 people responsible for consumer brand loyalty. The data in this study are collectives with questionnaires, interviews and literature. The data analysis used in this study is statistical analysis, such as linear regression with the SPSS 16.0 software program. The results of this study show that almost all variables of the marketing communication mix in brand loyalty in purchasing, and five of them such as advertising, sales promotion, personal sales, direct marketing, publicity, are significantly influenced.